Use of molecular ratios to identify changes in fatty acid composition of Miscanthus × giganteus (Greef et Deu.) plant tissue, rhizosphere and root-free soil during a laboratory experiment - Wiesenberg, G.; Schneckenberger, K.; Schwark, Lorenz; Kuzyakov, Y. (Pergamon, 2012)
Fatty acids (FAs) are abundant lipids in plants, microorganisms and soil. Depending on chain length they provide potential for evaluating different sources of C in soil: shoots, roots and microorganisms. This, together with their fast turnover and transformation in living and decaying plant tissues, suggests the use of FA molecular ratios as source indicators in soil. To evaluate the applicability of FAs as source indicators, their dynamics in plant tissue and soil were traced during a laboratory experiment using the highly productive perennial C 4 energy grass Miscanthus x giganteus (Greef et Deu.). For the comprehensive use of FAs as source indicators various ratios were calculated: fatty acid ratio (originally defined as carboxylic acid ratio: CAR), carbon preference index (CPI), average chain length (ACL) and unsaturated vs. saturated C 18 acids. The FA composition was specific for individual plant tissues as indicated by the CAR, with high values in roots and lower ones in the above ground plant tissue. Based on ACL values of rhizosphere, soil and roots, an enrichment in root derived FAs vs. root-free soil could be estimated. The rhizosphere contained 35-70% more plant derived FAs than root-free soil. The ACL showed potential for estimating root derived carbon in the rhizosphere. The study documents for the first time very fast spatial processes in soil related to plant growth, thereby strongly influencing the FA composition of soil. © 2012 Elsevier Ltd.